1999
DOI: 10.1103/physrevlett.82.1109
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ultraviolet Emission from233Uranium/T229horiumSamples

Abstract: from 233 uranium compounds and ascribed to an ultraviolet gamma-ray emission from the metastable 229 thorium daughter is actually N 2 discharge emission induced in the air surrounding the sample by the sample radioactivity. The UV spectrum from high elemental and isotopic purity 233 UO 3 reported here also exhibits a line at 391.3 nm that does not appear to be due to electric discharge N 2 emission. [S0031-9007(99)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…III, the chemical environment can significantly affect the half-life of the isomeric state [3]. It most likely explains why, given the currently accepted value for the isomeric transition energy, that many previous experiments performed in powders, solids and solutions produced null results [52][53][54][55][56]; similarly, non-VUV sensitive measurements could have been affected by internal conversion [57,58]. The internal conversion process could also have strong implications for the experiments reported in Refs.…”
Section: Importance Of the Electronic Conversion Decay Channelmentioning
confidence: 99%
“…III, the chemical environment can significantly affect the half-life of the isomeric state [3]. It most likely explains why, given the currently accepted value for the isomeric transition energy, that many previous experiments performed in powders, solids and solutions produced null results [52][53][54][55][56]; similarly, non-VUV sensitive measurements could have been affected by internal conversion [57,58]. The internal conversion process could also have strong implications for the experiments reported in Refs.…”
Section: Importance Of the Electronic Conversion Decay Channelmentioning
confidence: 99%
“…Their observed value for the isomeric transition were 3.5 eV [159] and likely 4 eV [160], respectively. However, in 1999, the studies of three different groups indicated that these conclusions must be based on the incorrect interpretation of experimental data [161][162][163]. G. M. Irwin and K. H. Kim later 5.1 Introduction of the agreed that their observation might result from the α-particle induced fluorescence of air, actually N 2 , surrounding the sample [161,162,164].…”
Section: Thorium Nucleusmentioning
confidence: 99%
“…In early experiments, two false detections of the decay of the isomer following α-decay of 233 U were reported [12,13], but it was quickly clarified that the observed light was luminescence induced by the background of α-radiation [14,15]. All further attempts at a direct observation of the optical transition failed.…”
Section: The Low-energy Isomer Ofmentioning
confidence: 99%
“…Recoil nuclei: The 229 Th isomer is populated with about 2% probability in the α-decay of 233 U and early attempts at an optical detection of the isomer decay have looked for light emission from 233 U sources [12,13], without success because of a strong background of radioluminescence [14,15]. This problem can be mitigated by using 229 Th recoil nuclei: If the α-decay of 233 U occurs close to the surface of the sample, the freshly produced 229 Th may be ejected and can be collected on an absorber (such as CaF 2 or MgF 2 , for instance) placed in front of the 233 U.…”
Section: Experimental Search For the 229 Th Nuclear Transitionmentioning
confidence: 99%